Energy and Protein Intake After Return Home in Colorectal Surgery Patients With an Enhanced Recovery Program: A Prospective Observational Study. (7th January 2021) - Hubert, Mégane; Gabriel, Dominique; El Khouda, Soraya; Coster, Marine; Routiaux, Clara; Hans, Gregory; Nihant, Nicole; Joris, Jean
Abstract : Background: In patients scheduled for colorectal surgery with an enhanced recovery program (ERP), feeding after returning home has been insufficiently investigated. The aim of this study was to measure energy and protein intake during the first month at home. Methods: Seventy adult patients scheduled for colorectal surgery with ERP were included. Calorie and protein intakes were calculated, and body weight was measured preoperatively and 3, 7, 15, and 30 days after discharge home. Data are mean ± SD or median (interquartile range). Results: Patient characteristics were age 60.0 ± 15.0 years, BMI = 25.9 ± 5.5 kg/m 2, and colon/rectum of 56/14. The duration of hospitalization was 3 (2–5) days. Calorie and protein intakes (21.9 [17.7–28.6] kilocalorie per kilogram of ideal body weight [kcal/kg IBW] and 0.81 [0.61–1.14] g/kg IBW) were significantly reduced ( P < .01) by 15% on day 3, compared with preoperative values, and then increased gradually to reach preoperative values after 1 month. Almost 50% of the patients failed to reach the calorie intake target of 25 kcal/kg IBW, and almost no patient reached the protein intake target of 1.5 g/kg IBW 30 days after discharge home. Weight loss after 30 days at home remained at −1.8 ± 2.7 kg. Conclusions: Colorectal surgery, even in an ERP, is associated with energy and protein intake below the targets recommended for the rehabilitation phase and results in weight loss. Whether nutrition counseling and prolonged administration of protein‐enriched oral supplements could accelerate weight gain needs to be explored.